2019
DOI: 10.1051/0004-6361/201834433
|View full text |Cite
|
Sign up to set email alerts
|

Search for gas from the disintegrating rocky exoplanet K2-22b

Abstract: Context. The red dwarf star K2-22 is transited every 9.14 hours by an object which is best explained by being a disintegrating rocky exoplanet featuring a variable comet-like dust tail. While the dust is thought to dominate the transit light curve, gas is also expected to be present, either from being directly evaporated off the planet or by being produced by the sublimation of dust particles in the tail. Aims. Both ionized calcium and sodium have large cross-sections, and although present at low abundance, ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Ito & Ikoma 2021), and note that gas absorption lines have not yet been detected in systems with dusty tails (e.g. Ridden-Harper et al 2019).…”
Section: Fiducial Model: Favourable Conditions For Dust Formationmentioning
confidence: 99%
“…Ito & Ikoma 2021), and note that gas absorption lines have not yet been detected in systems with dusty tails (e.g. Ridden-Harper et al 2019).…”
Section: Fiducial Model: Favourable Conditions For Dust Formationmentioning
confidence: 99%
“…Outside the midinfrared range, Lyman-α lines in the ultraviolet (e.g., Vidal-Madjar et al 2003;Lecavelier Des Etangs et al 2010;Ehrenreich et al 2015) and the absorption feature of excited metastable helium at 1083 nm (Seager & Sasselov 2000;Oklopčić & Hirata 2018;Spake et al 2018) are potentially useful to study whether the disintegrating planets possess an escaping atmosphere of hydrogen and helium. Detection of the line absorption features of sodium and calcium atoms would give us constraints on the gas loss and sublimation processes at work on disintegrating planets (Ridden-Harper et al 2019).…”
Section: Inferring the Planet Types From Tail Transmission Spectramentioning
confidence: 99%
“…Metal-rich gas must co-exist with the dusty effluents from CDEs (Rappaport et al 2012;Ridden-Harper et al 2019). A search for traces of this circumstellar gas in the Na D and Ca II infrared triplet lines in spectra of K2-22 yielded null results and a range of upper limits (Ridden-Harper et al 2019).…”
Section: Metal-rich Gas From Ablating Planetsmentioning
confidence: 99%
“…Metal-rich gas must co-exist with the dusty effluents from CDEs (Rappaport et al 2012;Ridden-Harper et al 2019). A search for traces of this circumstellar gas in the Na D and Ca II infrared triplet lines in spectra of K2-22 yielded null results and a range of upper limits (Ridden-Harper et al 2019). DMPP-1 is already known to exhibit circumstellar absorption (Staab et al 2019;Haswell et al 2019), so if the marginal transit detection reported herein does prove to be a CDE, this system will be the best yet known to trace the gas loss and sublimation processes discussed in Ridden-Harper et al (2019).…”
Section: Metal-rich Gas From Ablating Planetsmentioning
confidence: 99%